(untitled) (Journal of Economic Research & Business Administration, 2015)
It was proved by the global practice of doing business that entrepreneurship takes a big place in the national economy of any state since it defines to large extent the pace of economic growth, the structure and quality of the GDP. Main indicators of small and medium enterprise subjects’ activity in the Republic of Kazakhstan have been analyzed in the article: quantity of employees working in small and medium business, output in manufacturing industries, share of small and medium business in GDP of the country. There have been reflected financial and nonfinancial tools of state support of small and medium enterprise subjects, organization of centers for public service, national house of businessmen. Besides, there has been conducted valuation of activities in the plan of resolving procedures optimization. Today, the serious problem is absence of specific mechanism which allows determining the status of business entity.